Superficial hyperthermia plus radiotherapy as a palliative treatment of lymph nodes and skin cancer metastases - Miszczyk, Leszek; Owczarek, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2006)
Purpose: The aim of this study was an evaluation of hyperthermia plus radiotherapy as a treatment of lymph nodes and skin cancer metastases. Material and method: The material comprised of 48 metastatic lymph nodes and 17 skin metastases. The mean of tumor diameter was 3.8 cm. The most common pathological and clinical diagnoses were adenocarcinoma (N=27) and lung cancer (N=17) respectively. The mean follow-up was 3.5 months. Hyperthermia of 43°C was applied twice a week, for 45 minutes, using 915 MHz microwaves. Patients were irradiated five times a week (fd=2-4 Gy) up to 10-30 Gy and examined 2 and 6 weeks after the treatment and then every three months. Results: The biggest skin reaction was noted at the end of the treatment. In 43% of cases it was slight and in 32% intensive erythrema, in 10.5% blisters, in 2% brown skin and in 2% skin necrosis. The mean tumor diameter 2 weeks after the treatment was 2.9 cm and during the two following controls 1 and 3 months later it was 3.2 and 3.4 cm respectively. 7.5 months after the treatment the majority of tumors started to regrow (29% of progression). The highest rate of complete regression was noted 4.5 months after the treatment (25%). No significant differences in tumor regression regarding pathological examination, the number of hyperthermia sessions and metastases location were found. Conclusions: The results obtained allow us to draw the conclusion that hyperthermia combined with radiotherapy is an effective palliative treatment resulting in reasonable tumor regression and acceptable skin toxicity, however its ultimate advantage should be proven in a randomized trial comparing it to radiotherapy alone.